A KDM6A–KLF10 reinforcing feedback mechanism aggravates diabetic podocyte dysfunction - Lin, Chun‐Liang; Hsu, Yung‐Chien; Huang, Yu‐Ting; Shih, Ya‐Hsueh; Wang, Ching‐Jen; Chiang, Wen‐Chih; Chang, Pey‐Jium (EMBO molecular medicine, 2019)
Diabetic nephropathy is the leading cause of end‐stage renal disease. Although dysfunction of podocytes, also termed glomerular visceral epithelial cells, is critically associated with diabetic nephropathy, the mechanism underlying podocyte dysfunction still remains obscure. Here, we identify that KDM6A, a histone lysine demethylase, reinforces diabetic podocyte dysfunction by creating a positive feedback loop through up‐regulation of its downstream target KLF10. Overexpression of KLF10 in podocytes not only represses multiple podocyte‐specific markers including nephrin, but also conversely increases KDM6A expression. We further show that KLF10 inhibits nephrin expression by directly binding to the gene promoter together with the recruitment of methyltransferase Dnmt1. Importantly, inactivation or knockout of either KDM6A or KLF10 in mice significantly suppresses diabetes‐induced proteinuria and kidney injury. Consistent with the notion, we also show that levels of both KDM6A and KLF10 proteins or mRNAs are substantially elevated in kidney tissues or in urinary exosomes of human diabetic nephropathy patients as compared with control subjects. Our findings therefore suggest that targeting the KDM6A–KLF10 feedback loop may be beneficial to attenuate diabetes‐induced kidney injury. Synopsis Podocyte dysfunction is an early event in the development of diabetic nephropathy. This study reveals that activation of a KDM6A‐KLF10 positive feedback loop by hyperglycemia critically contributes to podocyte dysfunction. Blocking the KDM6A‐KLF10 signaling axis ameliorates diabetic kidney injury. Both KDM6A and KLF10 are up‐regulated in podocytes under diabetic conditions. Activation of the positive inter‐regulation between KDM6A and KLF10 results in repression of multiple podocyte‐specific marker proteins. Inactivation or podocyte‐specific knockout of KDM6A in mice attenuates diabetes‐induced kidney injury. Kidney injury is also reduced in KLF10‐knockout mice under diabetic conditions. Elevated levels of urinary exosomal KDM6A and KLF10 mRNAs are observed in human diabetic nephropathy patients relative to control subjects. Graphical Abstract Podocyte dysfunction is an early event in the development of diabetic nephropathy. This study reveals that activation of a KDM6A‐KLF10 positive feedback loop by hyperglycemia critically contributes to podocyte dysfunction. Blocking the KDM6A‐KLF10 signaling axis ameliorates diabetic kidney injury.